Exploring the effects of classical immune activation on circuit excitability and cell viability in the mouse brain - Tinelli, Sasha (Department of Human Biology, 2022)
Epilepsy directly affects approximately 50 million people globally and is the most common neurological disorder in sub-Saharan Africa, mainly due to high rates of neuroinfections and head trauma experienced by people in the region. A common factor in these causes of acquired epilepsy is their association with significant neuroinflammation, which is thought to drive the epileptogenic process. Although epilepsy exerts a heavy toll on the health, wellbeing and socio-economic outcomes of Africans, there are still major deficits in our understanding of how infections and inflammatory processes drive seizure development. Using the hippocampal organotypic brain slice culture model in mouse brains, I investigated the effects of classical immune activation on circuit excitability and cell viability. To initiate inflammation, I administered lipopolysaccharide (LPS), an endotoxin derived from gramnegative bacteria, and interferon-gamma (IFNy), a cytokine typically released by lymphocytes, to brain slices on varying time scales. I used enzyme-linked immune-sorbent assays to show that this reliably induced the release of the proinflammatory cytokines TNFα and IL-6 from the brain slices. I used patch-clamp electrophysiology to assess both the intrinsic electrical characteristics as well as the synaptic strength between pyramidal neurons after immune activation. I found no changes in the basic membrane properties of pyramidal neurons after short term neuroinflammation, but I did observe changes to the function of hippocampal networks at intermediate (24 hours) and lengthy (72 hours) time scales of immune activation in the form of significantly reduced spontaneous excitatory and inhibitory postsynaptic current frequencies and amplitudes. In addition, I developed an assay to determine neuronal survival to monitor the health of neurons in brain slices after immune activation and report that hippocampal organotypic brain slice cultures that were immuneactivated for 72 hours do not appear to experience either apoptotic or necrotic cell death. Taken together, these data constitute a valuable contribution towards understanding how inflammatory mechanisms drive changes to neuronal function, which could be relevant for understanding epileptogenesis in infectious and inflammatory causes of epilepsy.